Development of a towed fluorescence spectroscopy system for the detection of deposited polycyclic aromatic hydrocarbons. (1st August 2020) - Matsumoto, Akira; Liu, Xuanyu; Higuchi, Ken; Ikeda, Yoshichika; Arakawa, Hisayuki
Abstract: The Tōhoku earthquake and tsunami that struck on 11 March 2011 caused 22 fuel tanks around Kesennuma Bay in northern Japan to collapse. A sediment-contact-type fluorescence spectroscopy system was developed to observe the coastal distribution of polycyclic aromatic hydrocarbons (PAHs) deposited on the seafloor. A fluorescence maximum value of a sediment sample collected at Kesennuma Bay was considered as a "signal" whereas the ultraviolet reflectance was considered as a "noise". The fluorescence of the deposited PAHs was extracted through spectral subtraction. A sediment sample containing PAHs showed a broad maximum at a wavelength of 550 nm, which was attributed to the PAHs having a large number of benzene rings. In addition, the optimal probe angle that maximizes the signal-to-noise ratio was found to be 15°. The correlation between the PAH concentration and the fluorescence intensity was examined, and a formula for estimating the PAH concentration from the fluorescence intensity was obtained. With the developed method, the coastal distribution of PAHs deposited in Kesennuma Bay was observed in December 2015. The estimated PAH concentration (400–17, 500 μg/kg) was mostly on the order of 100–1, 000 μg/kg and locally exceeded 10, 000 μg/kg. With the developed instrument, it was possible to map the continuous distribution of PAHs on the seafloor over several hundred meters. Local fluctuations (on a scale of a few meters) in the concentration of PAHs were observed. The instrument and data processing techniques allowed for the high-resolution, quick and simple observation of PAHs in sediments. Highlights: A sediment-contact-type fluorescence spectroscopy system was developed. The system was used for the observation of PAHs in sediments. The spatial distribution of PAHs deposited in Kesennuma Bay was observed. Local fluctuations in the concentration of PAHs were observed. The instrument allowed for the quick and simple observation of PAHs in sediments.